Legal Challenges and Opportunities in World Trade Organization Agreements: A Comparative Analysis of Member States - Judijanto, Loso; Saliman, Abdul Rasyid; Sunggara, Muhamad Adystia; Handes, Agung Dhedy Dwi; Hendarto, Totok (International Journal of Science and Society, 2024)
The World Trade Organization (WTO) agreements have a broad and complex impact on its member countries, especially regarding trade policy and global economic justice. Legal challenges in implementing these agreements, including harmonization between national and international law, as well as domestic political and economic dynamics, add to the complexity of their implementation. In addition, the WTO agreements also offer significant opportunities for member countries, such as wider market access and increased foreign investment. This study aims to analyze the long-term impact of the WTO agreements on trade policy, economic justice, and sustainable development in its member countries. This study uses a qualitative approach, with data obtained from various relevant sources such as research results and previous studies, which are then processed and analyzed in depth. The results show that the WTO agreements significantly shape the direction of member countries' future trade policies, with a greater impact felt by developing countries. Global economic injustice has emerged as one of the consequences of the implementation of these agreements, where developed countries are better able to utilize WTO provisions. On the other hand, the environmental and social impacts of implementing the WTO agreements are concerns that require better integration into trade policy. Projections of future challenges suggest that the WTO must continue to adapt to global changes to remain relevant and effective. Overall, this study highlights the need for a balance between trade liberalization and the protection of social and environmental values ​​within the WTO framework.